The science case for LIGO-India. (15th December 2021) - Saleem, M; Rana, Javed; Gayathri, V; Vijaykumar, Aditya; Goyal, Srashti; Sachdev, Surabhi; Suresh, Jishnu; Sudhagar, S; Mukherjee, Arunava; Gaur, Gurudatt; Sathyaprakash, Bangalore; Pai, Archana; et al.
Abstract: The global network of gravitational-wave detectors has completed three observing runs with ∼50 detections of merging compact binaries. A third LIGO detector, with comparable astrophysical reach, is to be built in India (LIGO-Aundha) and expected to be operational during the latter part of this decade. Such additions to the network increase the number of baselines and the network SNR of GW events. These enhancements help improve the sky-localization of those events. Multiple detectors simultaneously in operation will also increase the baseline duty factor, thereby, leading to an improvement in the detection rates and, hence, the completeness of surveys. In this paper, we quantify the improvements due to the expansion of the LIGO global network in the precision with which source properties will be measured. We also present examples of how this expansion will give a boost to tests of fundamental physics.